Analisa Faktor Pengaruh Purchase Intention Melalui Engagement Sebagai Mediasi dan Brand Equity Sebagai Moderasi Pada Pengguna Media Sosial - Herdinasari, Renisa Ester; Christiarini, Renny (Universitas Batanghari, 2024)
This study aims to investigate the factors that influence the purchase intention of social media users. The research examines the impact of social presence, psychological distance, trust, engagement, social media marketing, electronic word of mouth (EWOM), and brand equity on purchase intention. Engagement is identified as a mediator, and brand equity as a moderator in the relationship. Data was collected from 290 reSPondents through the distribution of questionnaires and analyzed using the SmartPLS 3.0 program. The results of the data analysis indicate a positive correlation between trust, engagement, EWOM, and brand equity with purchase intention. However, there is no significant effect of social presence, psychological distance, and social media marketing. Additionally, the results showed no mediating effect of engagement, and the moderating impact of brand equity was less than 5%.